Potencial imunoterapêutico da proteína SmCyp do Schistosoma mansoni via polarização de macrófagos - Bonfante, Isadora (Universidade Federal de São Carlos, 2025)
The study of host-parasite interactions, such as those between Schistosoma mansoni and humans, is fundamental for the development of immunotherapies aimed at alleviating the severity of chronic infections associated with obesity, such as type 2 diabetes, or for stimulating the immune system in autoimmune diseases and cancer, as well as for the search for new vaccines. One of the immune system evasion mechanisms characteristic of S. mansoni infection is the shift of the immune response from Th1 (inflammatory) to Th2 (anti-inflammatory). Linked to this, there is a change in the macrophage activation profile, from classically activated (M1), linked to the inflammatory profile, to alternatively activated (M2), which contributes to attenuating the inflammatory response. This regulatory profile is being explored to identify promising molecules for the development of therapies that reduce chronic inflammation, in addition to contributing to the understanding of the mechanisms of action of vaccines against schistosomiasis. In this study, we evaluated the immunomodulatory potential of the recombinant protein SmCyp on macrophage polarization. This protein is a member of the cyclophilin family, known for its interaction with the immune system and regulatory function. To this end, we standardized the polarization of macrophages from the murine macrophage cell line J774A.1 for M1 and M2 phenotypes, with morphological analysis by Scanning Electron Microscopy (SEM) and confirmation by the quantitative determination of pro- and anti-inflammatory cytokines. Subsequently, assays were conducted with the recombinant protein SmCyp at concentrations of 25, 50, 100, 200, and 400 μg/mL and incubated for 24 and 48 hours to evaluate its modulatory potential in macrophages. Its influence on cell viability was investigated using the MTT and neutral red assays, as well as indirect nitric oxide (NO) production and the profile of inflammatory and anti-inflammatory markers, through the dosage of the cytokines TNF-α, IL-6, and IL-10, using the ELISA (Enzyme Linked Immunosorbent Assay) technique. The results indicated that SmCyp, at the concentrations tested, did not alter cell viability, either at 24 hours or at 48 hours. At 24 hours, an increase in TNF-α was observed, with values close to the M1 profile, but without stimulating the release of IL-6 or NO, suggesting a possible immunomodulatory potential. Based on the results obtained, SmCyp, at the concentrations and time points evaluated, showed moderate immune modulation potential, inducing TNF-α production within 24 hours, but without significant impact on nitric oxide production or the cytokines IL-6 and IL-10. These findings are crucial for deepening our understanding of the complex interactions between parasite and host, as well as the possible role of SmCyp in the immune response.
Immunotherapeutic potential of Schistosoma mansoni SmCyp protein via macrophage polarization
Keywords: Schistosoma mansoni; Macrófagos M1/M2; Imunomodulação; CIENCIAS BIOLOGICAS::IMUNOLOGIA